Penggunaan Bahasa Indonesia di Ruang Publik "Taman Bungkul Surabaya" - Azizatul Fara Dibah; Mila Reja Balqis; Nesvia Nissa Artanti; Rizvina Hadi Imani; Dwi Krisna Suci Nugroho (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
Indonesia has a lot of cultural and linguistic diversity, but the language that is often used widely in Indonesia is Indonesian. However, the use of Indonesian in public spaces is slowly being replaced by foreign languages. This can be seen through the use of English in many public spaces. Even though Indonesian has become the official state language and is widely used, there are still many individuals who have not mastered the use of Indonesian properly and correctly. Therefore, it is important to increase public awareness of the importance of using the Indonesian language correctly and appropriately, especially in public places, to prevent misunderstandings and misinterpretations between individuals and to maintain a good image of the nation in the eyes of the international community. Bungkul Park in Surabaya is one of the many public spaces that are of interest to the local community to visit. The use of Indonesian in Taman Bungkul Surabaya is very important so that everyone can communicate easily from various cultures and regions. Therefore, research was conducted regarding the use of Indonesian in public spaces, especially Taman Bungkul Surabaya using descriptive qualitative methods and observations. After observing the writings on the notice boards as well as several signs at several park points directly at Bungkul Park Surabaya, 15 signs were found indicating that the use of Indonesian around Bungkul Park Surabaya had used good Indonesian to provide information. on visitors. With that, visitors will find it helpful to have prohibitions, appeals, and instructions that have been found in Indonesian that are easy to understand and clear.